Helping Aged Victims of Crime (the HAVoC Study): Common Crime, Older People and Mental Illness – ERRATUM. Issue 2 (13th August 2015) - Serfaty, Marc; Ridgewell, Anna; Drennan, Vari; Brewin, Chris R.; Wright, Anwen; Laycock, Gloria; Blanchard, Martin
Abstract : The author list previously published for this article was incomplete when received by the journal. It should also have included Gerard Leavey, University College London, UK, as an author, as follows: Marc Serfaty, Anna Ridgewell, Vari Drennan, Chris R. Brewin, Gerard Leavey, Anwen Wright, Gloria Laycock, Martin Blanchard.